ANALISIS DAMPAK SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN KONTROL MANAJEMEN TERHADAP KINERJA MANAJERIAL (STUDI KASUS UD. USAHA MANDIRI) - Oktavianto, Eric; Solikah, Mar'atus; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2022)
This study seeks to find out how business management and management accounting information systems affect the performance of UD management. Independent Enterprises This study uses a quantitative approach and causal design techniques. This survey covers the entire UD workforce as its sample population. Usaha Mandiri consisted of 58 people, while the sample of UD employees was 30 people. The SPSS 23 program is then used to manage separate businesses that meet group quotas or quorums (sample). This is due to the large UD effect. The independent business management accounting information system has a significant impact on the effectiveness of UD's management. Independent business and management methods have a major impact on the effectiveness of UD management. independent company